Preserving the past, nurturing the future: a systematic literature review on the conservation and revitalization of Chinese historical town environments during modernization - Wen, Yanbo; Haider, Syed Arslan; Boukhris, Mohamed (Frontiers in Environmental Science, 2023)
The rapid urbanization occurring in China has brought increased attention from scholars towards the issue of revitalizing historical conservation of towns and adapting them to meet the needs of a modern city. In contemporary times, there is a notable emphasis among local residents and experts on the matter of effectively integrating the historical and cultural aspects, distinctive qualities, and traditional practices of a given locality with the demands and dynamics of urban life in a manner that preserves its historical essence. The present study focuses on several questions: What are the philosophical underpinnings and conceptual significance of conservation, regeneration, and urban evolution? What are the existing guidelines and implemented schemes of regeneration in China based on the principles of Space syntax theory and configurational analysis? The primary goal is to enhance the functionality of historical conservation of towns and improve the living environment for the local inhabitants. The study begins with the challenges faced in the historical conservation of towns in the backdrop of high-speed urbanization. Subsequently, it introduces the Space syntax theory as a theoretical perspective to address the problem of how to ensure the preservation of historical towns in linewith the demands of the modern cities in China. The current study used the bibliometric analysis method based on Scopus, Dimension and Web of science databases. The analysis was performed on R software and VOS viewer. Furthermore, only published articles, review papers and book chapters were selected that are published between 2000-2022. Lastly, the study suggests that the future research on the conservation of historical cities in China shall focus on policy formulation and community involvement in conservation and the regeneration of historic areas. The need to involve the public in the decision-making process of the future of their cities is imperative, since the locals are the end-users to every regeneration scheme, hence they are the key stakeholder responsible for ensuring the sustainability of their region.